2018
DOI: 10.1038/s41598-018-25346-3
|View full text |Cite
|
Sign up to set email alerts
|

Critical amino acids for the insecticidal activity of Vip3Af from Bacillus thuringiensis: Inference on structural aspects

Abstract: Vip3 vegetative insecticidal proteins from Bacillus thuringiensis are an important tool for crop protection against caterpillar pests in IPM strategies. While there is wide consensus on their general mode of action, the details of their mode of action are not completely elucidated and their structure remains unknown. In this work the alanine scanning technique was performed on 558 out of the total of 788 amino acids of the Vip3Af1 protein. From the 558 residue substitutions, 19 impaired protein expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 67 publications
6
51
0
Order By: Relevance
“…The five structural domains that were proposed from the three‐dimensional (3D) structure of the Vip3Af1 protein by alanine scanning mutagenesis analysis revealed that 19 residues prevent the expression of the VipAf1 protein. Another 19 substitutions reduced Spodoptera frugiperda toxicity and the latter 19 substitutions which were clustered between amino acids 167–272 and amino acids 689–741 also reduced toxicity to Agrotis segetum . Both the protoxin and the activated form of the Vip3 proteins are homo‐tetramers in solution .…”
Section: Structure Of Vip3a Proteinsmentioning
confidence: 99%
“…The five structural domains that were proposed from the three‐dimensional (3D) structure of the Vip3Af1 protein by alanine scanning mutagenesis analysis revealed that 19 residues prevent the expression of the VipAf1 protein. Another 19 substitutions reduced Spodoptera frugiperda toxicity and the latter 19 substitutions which were clustered between amino acids 167–272 and amino acids 689–741 also reduced toxicity to Agrotis segetum . Both the protoxin and the activated form of the Vip3 proteins are homo‐tetramers in solution .…”
Section: Structure Of Vip3a Proteinsmentioning
confidence: 99%
“…One of the main reasons for this is the lack of a high-resolution three-dimensional structure, which significantly impedes detailed molecular level functional and mechanistic studies and thus limits the development of their insecticidal potential. Accordingly, many groups have made great efforts to obtain or predict the atomic structure of Vip3A 21, 27, 28, 32, 33 . However, high-resolution crystal structure of Vip3 toxin family is still missing.…”
Section: Discussionmentioning
confidence: 99%
“…The scavenger receptor class C like protein (Sf-SR-C) and the fibroblast growth factor receptor (Fgfr) have been reported as potential receptors for Vip3A 13, 14 . However, although some in silico modeling efforts and low resolution cryo-EM structures have attempted to obtain structural insight for these toxins, the atomic structure of Vip3A is still not available, which makes it difficult to reveal the relationship between their structure and function 27, 28, 32, 33 .…”
Section: Introductionmentioning
confidence: 99%
“…So far, the structure of Vip3A toxin has not been solved. Its structural information has been derived only by in-silico modeling [14,15], though the structure of the Vip3B was recently reported [16]. Studies on proteolytic activation of Vip3A proteins have shown that by a proteolytical process Vip3A protoxins are cleaved to become several major fragments, generally including fragments of 62-66 kDa, 45 kDa, 33 kDa and 19-22 kDa [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of Vip3Af by Ala scanning to cover 558 out of the 788 residues showed that the most Ala substitutions in Vip3Af significantly decreased the insecticidal activity, and the proteolytically processed fragments of the Vip3Af substitution mutants displayed six different patterns by SDS-PAGE analysis [14]. Further analysis indicated that Vip3Af mutants with different proteolytic patterns could form a variety of oligomeric products [21].…”
Section: Introductionmentioning
confidence: 99%